The Rule of Law, The Rule of Conflict? Hong Kong and Democracy—Past and Present Revisited - Sadowski, Mirosław (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2019)
“The rule of law is essential to Hong Kong’s future” — declared the last governor of Hong Kong, Christopher Patten, a few years before the city’s handover to China. The rule of law, obviously, is essential to the future of any legal entity. However, one has to ask what happens if the law that rules is imperfect. It then inevitably leads to conflicts. The purpose of this paper is to investigate how efficiently has the rule of law ‘ruled’ in Hong Kong since the transition, with a special focus on the situations when law itself led to conflicts. In his analysis the author concentrates on the post-colonial influences of the past, People's Republic of China’s influences of the present, and outlines possible scenarios for the future of the Chinese Special Administrative Region, while highlighting the question of democracy. The article is divided into two main parts–theoretical, composed of one chapter, and analytical, composed of two chapters. In the first part of the article the author reviews various understandings of the notions of the rule of law and of conflict, introducing the theoretical framework for further investigations. The second chapter of the article is devoted to the question of the rule of law in the semi-autonomous city. The author first explains why its explicit conceptualisation was revolutionary in Hong Kong at this particular moment, and then shows how it has been eroding ever since 1997. In the third chapter of the paper, the author focuses on the situations in Hong Kong when law itself has provoked conflicts — notably the recent oath-swearing dispute — and analyses them. The fourth, concluding part of the paper the author ventures to make predictions on the future of the legal systems, democracy, and thus the lives of the citizens of the Fragrant Harbour.